Manufacturing process of high-performance monocrystalline silicon nano wafer
Through refined single crystal silicon wafers, multi -stage cleaning, advanced nano structure manufacturing and adaptive thermal treatment process, combined with surface functionalization and multi -layered and high -precision packaging, the mechanical strength, surface quality and environment of single crystal silicon nano -chip manufacturing are solved The problem of insufficient stability has achieved high -performance and long -term reliability nano -chip manufacturing.
Patent Information
- Application Number
- CN202411418990.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-24
AI Technical Summary
The existing single-crystal silicon nanochip manufacturing processes have problems with insufficient mechanical strength, surface quality and environmental stability in silicon wafer preparation, nanostructure manufacturing, and doped packaging.
Preparation, multi -stage cleaning, advanced nano -structure manufacturing and adaptive thermal treatment process are used with refined single crystal silicon wafers, combined with surface functionalization and multi -level and high -precision packaging to enhance the mechanical strength, electrical performance and environmental tolerance of the chip.
The surface quality, mechanical strength and electrical properties of single crystal silicon nanowafers are significantly improved, and their long-term reliability and anti-oxidation and anti-corrosion properties in complex environments are enhanced.
Smart Images

Figure CN119349499A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of microelectronics manufacturing, in particular to a high-performance single-crystal silicon nano-wafer manufacturing process. Background Art
[0002] Single-crystal silicon nanochips are important materials for modern electronic and optoelectronic devices and are widely used in semiconductors, sensors, and high-precision optical components. The manufacture of high-performance single-crystal silicon nanochips requires extremely high precision and consistency in multiple process steps such as preparation, surface treatment, nanostructure manufacturing, doping, and packaging to ensure the mechanical strength, surface purity, and electrical properties of the chip, thereby meeting the needs of high-performance devices.
[0003] The existing single-crystal silicon nanochip manufacturing process usually includes cutting of single-crystal silicon rods, chemical mechanical polishing to reduce surface defects, and surface passivation treatment to improve chemical stability. Nanostructure manufacturing mainly relies on electron beam lithography and reactive ion etching technology to achieve the formation of complex patterns by finely controlling the etching depth and sidewall angle. Doping and heat treatment use traditional thermal annealing to activate dopants and repair lattice defects at the same time. Finally, through the packaging step, polymer or metal materials are used to physically protect the chip to improve the environmental stability and anti-interference ability of the device.
[0004] However, the existing technology still has several shortcomings in the manufacture of single-crystal silicon nanochips: first, in the process of silicon wafer preparation, surface microcracks and residual stresses are difficult to completely eliminate, resulting in insufficient mechanical strength and surface quality; second, the pattern overlay and sidewall control accuracy in nanostructure manufacturing are limited, affecting the functionality and integration of the device; in addition, traditional doping and packaging technologies are not effective in improving the environmental stability and long-term reliability of chips, especially in complex or extreme environments, and are prone to oxidation, corrosion and electrical isolation failure. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a high-performance single-crystal silicon nanochip manufacturing process. The present invention significantly improves the surface quality, mechanical strength and electrical properties of the chip through processes such as refined single-crystal silicon wafer preparation, multi-stage cleaning, advanced nanostructure manufacturing and adaptive heat treatment; and enhances the environmental tolerance and long-term reliability of the nanostructure through surface functionalization and multi-level high-precision packaging, effectively solving the deficiencies of the prior art in terms of accuracy, stability and tolerance.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A high-performance single-crystal silicon nanochip manufacturing process comprises the following steps:
[0007] Prepare single crystal silicon wafers, and obtain high-quality single crystal silicon wafers through fine cutting, chemical mechanical polishing and surface residual stress elimination treatment;
[0008] Multi-stage cleaning and surface treatment to remove surface contaminants through a combination of molecular chromatography, electric field-assisted ultrasonic cleaning, and low-temperature plasma cleaning;
[0009] Nanostructure manufacturing, using multi-stage electron beam lithography, segmented reactive ion etching and adaptive deep etching control to form complex nanostructures;
[0010] Doping and heat treatment, using dynamic time segmented annealing and multi-scale environmental control for doping activation and defect repair;
[0011] Surface functionalization and packaging improve the environmental stability and long-term reliability of chips through self-assembled monolayer deposition, molecular beam epitaxy and multi-level high-precision packaging.
[0012] Preferably, the dynamic time segmented annealing and multi-scale environmental regulation include:
[0013] The annealing temperature and time are adjusted in stages. The temperature is controlled at 300-500 degrees Celsius in the initial stage, and stress is released by low-frequency short pulses with each pulse lasting 5-10 seconds.
[0014] The temperature in the middle stage is set at 600-800 degrees Celsius, and the activation and diffusion of dopants are achieved by increasing the pulse frequency to once every 10-20 seconds and controlling the pulse temperature fluctuation at 50-100 degrees Celsius;
[0015] In the final stage, the temperature is controlled at 800-1000 degrees Celsius, the pulse frequency is gradually reduced and the temperature step method is used to adjust 10-20 degrees Celsius every 5 minutes to optimize the repair of lattice defects;
[0016] Combining real-time stress sensing and defect analysis data, the annealing parameters are adjusted through a reinforcement learning algorithm to achieve an adaptive annealing process.
[0017] Preferably, the multi-scale environmental regulation includes:
[0018] In the initial stage, high-purity argon gas is used for overall atmosphere control, with a flow rate of 1 to 2 liters per minute;
[0019] In the mid-term, the molecular sieve adjustment system is used to fine-tune the atmosphere through molecular diversion technology, removing the oxygen concentration to less than 5ppm and accurately controlling the hydrogen concentration at 0.1-0.3%;
[0020] In the final stage, the amount of hydrogen introduced is fine-tuned to 10-100 ml / min through a local regulating valve to promote surface passivation and defect repair.
[0021] Preferably, the preparation of a single crystal silicon wafer comprises:
[0022] The Czochralski method is used to grow single crystal silicon rods, and the oxygen content is controlled to be less than 1ppm through magnetic field induction technology;
[0023] Cut the single crystal silicon rod into silicon wafers with a thickness of 50 to 300 microns by vibration-controlled wire saw or laser cutting, with a cutting accuracy of ±2 microns;
[0024] Chemical mechanical polishing combined with weak acid treatment is used to eliminate surface microcracks. 10 to 50 nanometers of nano-silicon dioxide is added to the polishing liquid, and the polishing pressure is controlled at 0.1 to 0.5 Newtons per square centimeter.
[0025] A low-temperature short-time annealing is performed with the temperature controlled at 300-500 degrees Celsius for 10-20 minutes to reduce residual stress, and the final surface roughness is less than 1 nanometer.
[0026] Preferably, the multi-stage cleaning and surface treatment comprises:
[0027] A three-step cleaning process using a mixed solution of nitric acid, hydrofluoric acid, and ethanol gradually removes heavy metal ions, oxides, and organic matter;
[0028] Ultrapure water is used for rinsing, and ultrapure water is dynamically regenerated by electrolysis. The rinsing time is 5 to 10 minutes;
[0029] Low-temperature plasma cleaning uses alternating hydrogen and oxygen plasma treatments to ensure complete removal of residual contaminants.
[0030] Preferably, the cleaning further comprises:
[0031] Ammonium hydroxide and hydrogen peroxide are added to the cleaning solution, and cleaning is performed with the assistance of dual-frequency ultrasound at 20 to 80 kHz and an electric field at 10 to 20 volts per centimeter to improve the desorption efficiency of particles and organic matter;
[0032] By real-time monitoring of the conductivity of the cleaning fluid, the cleaning effect is ensured to be continuous and stable, and the cleaning fluid is automatically replaced.
[0033] Preferably, the nanostructure manufacturing comprises:
[0034] Using multi-level electron beam lithography and multi-layer mask alignment technology, the mask alignment accuracy is controlled within ±5 nanometers to achieve the superposition of complex nano patterns;
[0035] Using reactive ion etching, the etching parameters are monitored by a real-time feedback system to ensure consistent etch depth and sidewall smoothness.
[0036] Preferably, the nanostructure manufacturing further comprises:
[0037] Implement ultra-fast pulse etching, with each pulse lasting 1 to 5 milliseconds, and control the etching effect by adjusting the pulse interval and frequency;
[0038] Combined with a multi-layer mask protection strategy, the lateral corrosion of the mask and the sidewall erosion of the pattern are reduced to ensure the verticality and precision of the nanostructure.
[0039] Preferably, the surface functionalization comprises:
[0040] Coating a self-assembled monolayer on the surface of the nanostructure, using atomic layer deposition or molecular beam epitaxy to deposit a protective layer with a thickness of 1 to 5 nanometers;
[0041] Real-time thickness monitoring ensures uniformity and surface smoothness of the protective layer, improving the environmental tolerance of the nanostructure.
[0042] Preferably, the packaging includes:
[0043] Use low dielectric constant polyimide materials for stress-free packaging, and reduce mechanical stress by precisely controlling temperature and pressure;
[0044] Multi-layer shielding packaging is implemented to provide electromagnetic shielding, insulation and mechanical protection for the device through a combination of metal layers, insulating layers and polymer layers.
[0045] The present invention provides a high-performance single-crystal silicon nano-wafer manufacturing process, which has the following beneficial effects:
[0046] 1. The present invention significantly improves the surface quality and purity of silicon wafers through refined single crystal silicon wafer preparation and multi-stage cleaning treatment, effectively reduces microcracks and residual stress, ensures high precision and consistency of nanostructure manufacturing, and improves the mechanical strength and electrical properties of nano wafers.
[0047] 2. The present invention achieves high-precision superposition of complex nano-patterns and control of sidewall smoothness by adopting a nano-structure manufacturing process that combines multi-level electron beam lithography with adaptive deep etching, thereby improving the verticality and resolution of the nano-structure, thereby enhancing the functionality and integration of nano-devices.
[0048] 3. The present invention uses dynamic segmented annealing and multi-scale environmental regulation to perform doping and defect repair, as well as a combination of surface functionalization and multi-level high-precision packaging, to effectively improve the environmental tolerance and long-term stability of the nanochip, enhance its anti-oxidation, anti-corrosion and electrical isolation properties, and ensure the reliability of the device in a variety of complex environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0050] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Please see attached Figure 1 The embodiment of the present invention provides a high-performance single-crystal silicon nanochip manufacturing process, comprising the following steps:
[0052] Preparation of single crystal silicon wafers, through fine cutting, chemical mechanical polishing and surface residual stress elimination treatment to obtain high-quality single crystal silicon wafers. Fine cutting can significantly reduce micro cracks and mechanical damage in silicon wafers, improve the surface quality and flatness of silicon wafers, and lay a good foundation for subsequent nanostructure manufacturing and doping treatment. At the same time, the elimination treatment further eliminates residual stress and improves the overall mechanical strength and stability of the wafer;
[0053] Multi-stage cleaning and surface treatment, through the combination of molecular chromatography, electric field assisted ultrasonic cleaning and low-temperature plasma cleaning to remove surface pollutants, through multi-stage cleaning and surface treatment, can effectively remove various pollutants on the surface of silicon wafers, improve the surface cleanliness, and at the same time, combined with the surface activation effect of low-temperature plasma cleaning, further improve the chemical stability of the surface, providing an excellent foundation for the pattern transfer of nanostructures;
[0054] Nanostructure manufacturing uses multi-level electron beam lithography, segmented reactive ion etching and adaptive deep etching control to form complex nanostructures. Multi-level electron beam lithography is combined with segmented reactive ion etching, and adaptive etching control technology ensures the morphology consistency of each layer of nanostructure, greatly improving the electrical performance and integration of the device, meeting the requirements of high-performance nanodevices;
[0055] Doping and heat treatment, using dynamic time segmented annealing and multi-scale environmental control for doping activation and defect repair. Dynamic time segmented annealing and multi-scale environmental control can achieve fine control of the doping process, effectively activate doping atoms and repair lattice defects, ensuring the uniformity and depth consistency of doping. This precise heat treatment method greatly improves the electrical properties of nanochips and reduces the impact of defects on device performance;
[0056] Surface functionalization and packaging improve the environmental stability and long-term reliability of the chip through self-assembled monolayer deposition, molecular beam epitaxy and multi-level high-precision packaging. The combination of self-assembled monolayer and high-precision protective layer prevents the external environment from corroding the nanostructure, while multi-layer shielding packaging ensures the reliability and performance stability of the device in complex working environments and extends its service life.
[0057] Please see attached Figure 1 In a preferred embodiment of the present invention, dynamic time segmented annealing and multi-scale environment control include:
[0058] The annealing temperature and time are adjusted in stages. The temperature is controlled at 300-500 degrees Celsius in the initial stage, and stress is released by low-frequency short pulses with each pulse lasting 5-10 seconds. In the initial stage, the annealing temperature is controlled at 300-500 degrees Celsius, and heat treatment is performed by low-frequency short pulses. Each pulse lasts for 5 to 10 seconds, and the pulse frequency is low, so as to gradually release the residual stress inside the silicon wafer. The annealing treatment at this stage effectively releases the residual stress accumulated in the previous processing process, reduces the stress concentration and microcrack formation inside the silicon wafer, and thus can improve the mechanical strength and stability of the silicon wafer;
[0059] The temperature in the middle stage is set at 600-800 degrees Celsius. By increasing the pulse frequency to once every 10-20 seconds, the pulse temperature fluctuation is controlled at 50-100 degrees Celsius to achieve activation and diffusion of dopants. In this temperature range, the pulse frequency is increased and pulse heat treatment is performed every 10-20 seconds. Frequent temperature pulses enable dopant atoms to obtain sufficient kinetic energy, successfully activate dopants and achieve uniform diffusion in the silicon wafer. This dynamic control method not only speeds up the doping activation process, but also prevents the aggregation or precipitation of dopant atoms at high temperatures, thereby improving doping uniformity and electrical properties, and providing guarantees for the conductivity and carrier mobility of silicon wafers.
[0060] In the final stage, the temperature is controlled at 800-1000 degrees Celsius, the pulse frequency is gradually reduced, and the temperature step method is used to adjust 10-20 degrees Celsius every 5 minutes to optimize the repair of lattice defects. In this stage, the pulse frequency is gradually reduced, and the temperature step method is used, that is, 10-20 degrees Celsius is adjusted every 5 minutes to gradually reduce the intensity of heat treatment and accurately repair lattice defects. The annealing treatment in the final stage realizes the meticulous repair of the silicon wafer lattice structure, minimizes the existence of lattice defects, and ensures the uniform distribution of doped atoms in the silicon wafer. The application of the temperature step method effectively avoids the thermal stress damage caused by high-temperature annealing, thereby improving the structural integrity and electrical properties of the silicon wafer;
[0061] Combining real-time stress sensing and defect analysis data, the annealing parameters are adjusted through the reinforcement learning algorithm to achieve an adaptive annealing process. The application of the reinforcement learning algorithm has ushered the annealing process into a new era of intelligence and adaptability. It not only improves the degree of automation of the process, but also greatly improves the quality and consistency of the wafer through continuous optimization of the annealing path. The algorithm ensures that each annealing parameter can be finely adjusted according to the real-time status, avoiding process deviations and quality problems that may be caused by traditional static control, and comprehensively improving the performance of single-crystal silicon nanowafers.
[0062] Please see attached Figure 1 In a preferred embodiment of the present invention, multi-scale environmental control includes:
[0063] In the initial stage, high-purity argon is used for overall atmosphere control, with a flow rate of 1 to 2 liters per minute. As an inert gas, argon will not react with silicon wafers, and can provide a stable protective environment to avoid oxidation and other adverse reactions. This range is used to reduce the impact of the external atmosphere on the surface of the silicon wafer during the heating process, avoid the formation of an oxide layer, and thus ensure the purity and surface quality of the silicon wafer. The inert protective effect of argon ensures the structural stability of the silicon wafer in subsequent high-temperature treatment and provides a pollution-free basic environment for the doping process;
[0064] In the mid-term stage, the molecular sieve adjustment system is used to fine-tune the atmosphere through molecular diversion technology to remove oxygen concentration to less than 5ppm, and accurately control the hydrogen concentration at 0.1-0.3%. In this stage, the molecular sieve adjustment system and molecular diversion technology are used to accurately control the oxygen and hydrogen content in the atmosphere. The molecular sieve system removes oxygen and other impurity gases by selectively adsorbing and separating gas components. First, the molecular sieve material is used to reduce the oxygen concentration in the atmosphere to less than 5ppm. This efficient adsorption can quickly remove the oxidizing components in the annealing environment and prevent the secondary oxidation of the silicon wafer. At the same time, the chemical state of the silicon wafer surface is further optimized by utilizing the reduction characteristics of hydrogen. Hydrogen can effectively passivate the dangling bonds and other active sites on the silicon wafer surface, thereby reducing defect formation. By removing trace oxygen and accurately controlling the hydrogen concentration, unnecessary oxidation reactions are avoided and the passivation effect of the silicon wafer surface is improved.
[0065] In the final stage, the amount of hydrogen introduced is fine-tuned to 10 to 100 ml per minute through a local regulating valve to promote surface passivation and defect repair. The fine control of the amount of hydrogen introduced by the local regulating valve optimizes the surface passivation of the silicon wafer, effectively repairs lattice defects and improves surface quality. The hydrogen treatment in the final stage not only further reduces the surface state density, but also greatly reduces the leakage current of the device under high temperature conditions, enhancing the electrical stability and long-term reliability of the silicon wafer.
[0066] Please see attached Figure 1In a preferred embodiment of the present invention, preparing a single crystal silicon wafer comprises:
[0067] The Czochralski method is used to grow single crystal silicon rods, and the oxygen content is controlled to be less than 1ppm through magnetic field induction technology. The Czochralski method combined with magnetic field induction technology effectively reduces the content of oxygen impurities in the silicon rods and reduces the lattice defects caused by oxide inclusions. This high-purity single crystal silicon rod provides a better material basis for subsequent cutting and processing, which helps to improve the electrical properties and structural integrity of the final silicon wafer;
[0068] The single crystal silicon rod is cut into silicon wafers with a thickness of 50 to 300 microns by vibration-controlled wire saw or laser cutting, with a cutting accuracy of ±2 microns. Through precise cutting control, the surface damage layer and microcracks of the silicon wafer are significantly reduced, thereby reducing the need for surface repair in subsequent processing. The vibration-controlled wire saw and laser cutting technology not only improves the cutting accuracy, but also reduces the stress introduced by processing, thereby improving the structural integrity and service life of the silicon wafer;
[0069] Chemical mechanical polishing combined with weak acid treatment is used to eliminate surface microcracks. 10 to 50 nanometers of nano-silicon dioxide is added to the polishing liquid, and the polishing pressure is controlled at 0.1 to 0.5 Newtons per square centimeter. Through precise cutting control, the surface damage layer and microcracks of the silicon wafer are significantly reduced, thereby reducing the need for surface repair in subsequent processing. Vibration-controlled wire saw and laser cutting technology not only improves cutting accuracy, but also reduces the stress introduced by processing, improves the structural integrity and service life of silicon wafers. Chemical mechanical polishing combined with weak acid treatment can significantly reduce microcracks and rough areas on the surface of silicon wafers to achieve nano-level finish. This treatment method not only improves the mechanical strength of silicon wafers, but also greatly improves their surface quality, providing a high-quality substrate for subsequent nanostructure manufacturing;
[0070] Low-temperature short-time annealing is carried out with the temperature controlled at 300-500 degrees Celsius for 10-20 minutes to reduce residual stress. The final surface roughness is less than 1 nanometer. This temperature range can promote stress relief of the silicon lattice without causing reconstruction or excessive diffusion of the crystal structure. At the same time, through this short-time treatment, the purpose of stress release can be achieved in a shorter time and potential damage to the silicon wafer caused by long-term high temperature can be avoided. The annealed silicon wafer not only has higher mechanical strength, but also has better thermal stability and chemical stability, and ensures the dimensional stability and performance consistency of the silicon wafer in subsequent high-temperature processing.
[0071] Please see attached Figure 1 In a preferred embodiment of the present invention, the multi-stage cleaning and surface treatment comprises:
[0072] A three-step cleaning is performed using a mixed solution of nitric acid, hydrofluoric acid and ethanol to gradually remove heavy metal ions, oxides and organic matter. A nitric acid solution is used for preliminary cleaning to remove heavy metal ions attached to the surface of the silicon wafer. Hydrofluoric acid is then used to clean the surface of the silicon wafer to remove the natural oxide layer and oxides formed during the processing. Finally, ethanol is used to clean the surface to remove organic matter remaining on the surface and moisture that may be introduced during the cleaning process. Rapid volatility ensures that the surface of the silicon wafer dries quickly to avoid redeposition of water marks and pollutants. This multi-step cleaning method ensures a high degree of cleanliness on the surface of the silicon wafer, providing the best surface state for subsequent nanostructure manufacturing. While removing oxides and organic matter, it also ensures the activity and uniformity of the surface, improving the effectiveness of subsequent treatments.
[0073] Ultrapure water is used for rinsing, and ultrapure water is dynamically regenerated by electrolysis. The rinsing time is 5 to 10 minutes. This step adopts quantitative flow control, and the flow rate is set at 1 to 2 liters per minute to ensure uniform and sufficient rinsing effect. Ultrapure water rinsing combined with dynamic regeneration by electrolysis can effectively remove chemical cleaning residues and potential contamination, maintain ultra-high cleanliness of the silicon wafer surface, not only ensure the surface activity and consistency of subsequent treatments, but also prevent secondary contamination caused by residues after chemical cleaning, greatly improving the overall cleaning effect;
[0074] Low-temperature plasma cleaning is carried out, using hydrogen and oxygen plasma alternating treatment to ensure that residual contaminants are completely removed. Hydrogen plasma is reducing and can passivate dangling bonds on the surface of the silicon wafer and reduce the surface state density, while oxygen plasma removes organic residues through oxidation reactions and improves surface cleanliness and activity. Low-temperature plasma cleaning combined with alternating treatment of hydrogen and oxygen can effectively remove trace organic matter and other residual contaminants on the surface of the silicon wafer, ensuring that the silicon wafer achieves ultra-high surface cleanliness. At the same time, the passivation effect of hydrogen plasma can reduce surface dangling bonds and improve the chemical stability and electrical properties of the silicon wafer.
[0075] Please see attached Figure 1 In a preferred embodiment of the present invention, the cleaning further comprises:
[0076] Ammonium hydroxide and hydrogen peroxide are added to the cleaning solution, and cleaning is performed under the assistance of dual-frequency ultrasound at 20 to 80 kHz and an electric field at 10 to 20 volts per centimeter to improve the desorption efficiency of particles and organic matter. Ammonium hydroxide, as a weak alkaline reagent, can neutralize and dissolve acidic residues on the surface of the silicon wafer, and react with hydrogen peroxide to generate active oxygen substances, which can effectively oxidize organic pollutants and dissolve them into the cleaning solution. The selective oxidation ability of the mixed cleaning solution ensures efficient removal of organic matter and particles without damaging the surface of the silicon wafer. By adding ammonium hydroxide and hydrogen peroxide to the cleaning solution and combining dual-frequency ultrasound and electric field-assisted cleaning, the desorption efficiency of particles and organic pollutants is effectively enhanced, thereby improving the depth and breadth of cleaning, and improving the cleanliness and surface quality of the silicon wafer, providing a clean surface condition for subsequent nano-processing steps;
[0077] By real-time monitoring of the conductivity of the cleaning fluid, the continuous stability of the cleaning effect is ensured, and the cleaning fluid is automatically replaced. By setting a reasonable conductivity monitoring threshold, when the conductivity exceeds the preset range (such as 5 to 10 microSiemens per centimeter), the system will automatically start the regeneration or replacement program of the cleaning fluid. By real-time monitoring of the conductivity of the cleaning fluid and automatic replacement of the cleaning fluid, the continuous stability of the cleaning effect is effectively guaranteed. This mechanism can promptly detect and correct possible efficiency reduction or liquid failure problems during the cleaning process, ensuring the consistency and efficiency of the cleaning process.
[0078] Please see attached Figure 1 In a preferred embodiment of the present invention, the nanostructure manufacturing comprises:
[0079] Multi-level electron beam lithography and multi-layer mask alignment technology are used to control the mask alignment accuracy within ±5 nanometers to achieve the superposition of complex nano patterns. Electron beam lithography can accurately control the size and shape of the exposure area, so it is particularly suitable for manufacturing nano structures with fine details and high-density patterns. Multi-layer mask alignment technology combines the use of hard masks (such as chromium, silicon nitride) and soft masks (such as photoresist) to achieve multiple superimposed exposures. The hard mask provides a basis for high corrosion resistance and high resolution, while the soft mask is easy to remove and correct. Each layer of mask is scanned and fine-tuned multiple times by the alignment system. The feedback information of the control system alignment is used to ensure that each layer of pattern can be accurately superimposed on the basis of the previous layer of pattern, thereby constructing a complex three-dimensional nano structure. Multi-level electron beam lithography and multi-layer mask alignment technology can achieve accurate superposition of complex nano patterns, improve the design freedom and manufacturing accuracy of the nano structure, control the alignment accuracy within ±5 nanometers, and ensure the high consistency and fineness of each layer of nano patterns.
[0080] Using reactive ion etching, the etching parameters are monitored through a real-time feedback system to ensure the consistency of etching depth and sidewall smoothness. By using reactive ion etching technology combined with a real-time feedback system, the etching depth and sidewall smoothness can be effectively controlled to ensure high precision and consistency of the nanostructure. This technical combination not only achieves the precise transfer of complex nanopatterns, but also reduces sidewall defects and roughness, thereby improving the electrical properties and mechanical stability of the nanostructure.
[0081] Please see attached Figure 1 In a preferred embodiment of the present invention, the nanostructure manufacturing comprises:
[0082] Ultra-fast pulse etching is implemented, with each pulse lasting 1 to 5 milliseconds. The etching effect is controlled by adjusting the pulse interval and frequency. This ultra-short pulse mode can provide high energy density in a very short time, thereby accurately removing the surface material of the silicon wafer. By optimizing the pulse interval and frequency, energy accumulation control during the etching process can be achieved, thereby avoiding the thermal effect and sidewall damage that may be caused by traditional continuous etching, thereby achieving fine processing of nanostructures, effectively reducing the thermal effect and material damage caused by continuous heating during traditional etching, and ensuring the verticality and edge smoothness of the nanostructure;
[0083] Combined with a multi-layer mask protection strategy, the lateral corrosion of the mask and the sidewall erosion of the pattern are reduced to ensure the verticality and accuracy of the nanostructure. First, a hard mask material (such as chromium or silicon oxide) is deposited on the surface of the silicon wafer with a thickness of 50 to 200 nanometers through physical vapor deposition (PVD) or chemical vapor deposition (CVD) processes. This layer of hard mask provides high corrosion resistance protection and can resist physical and chemical attacks in etching reactions. Multi-layer masks can provide excellent etching resistance, extend the service life of the mask, and reduce the frequency of mask replacement during processing. By reducing sidewall erosion, the size control of the nanostructure is more precise and the edges are smoother, which helps to improve the performance and stability of nano devices.
[0084] Please see attached Figure 1 In a preferred embodiment of the present invention, the surface functionalization comprises:
[0085] A self-assembled monolayer is coated on the surface of the nanostructure, and a protective layer with a thickness of 1 to 5 nanometers is deposited using atomic layer deposition or molecular beam epitaxy technology. The coating of the self-assembled monolayer can significantly improve the surface chemical properties of the silicon nanostructure, and reduce the surface state density by passivating the dangling bonds on the silicon surface and reducing surface defects. The self-assembled monolayer not only enhances the chemical stability of the surface, but also improves the tolerance of the nanostructure in humid, oxidative and corrosive environments. The ultra-thin protective layer is deposited on the surface of the nanostructure by atomic layer deposition or molecular beam epitaxy technology, which effectively improves the mechanical strength and environmental stability of the structure. The protective layer can prevent oxidation, corrosion and mechanical damage, while maintaining the surface smoothness and electrical properties of the nanostructure. The uniformity and high quality of the layer ensure the long-term stable operation of the nanostructure in harsh environments;
[0086] Real-time thickness monitoring ensures the uniformity and surface smoothness of the protective layer and improves the environmental tolerance of the nanostructure. The application of the real-time thickness monitoring system ensures the thickness uniformity and surface smoothness of the protective layer, effectively reducing thickness fluctuations and surface defects during the deposition process. This precision control improves the stability and performance consistency of the nanostructure in different environments, ensuring that the device maintains excellent functional characteristics during its service life.
[0087] Please see attached Figure 1 In a preferred embodiment of the present invention, the package comprises:
[0088] Use low dielectric constant polyimide materials for stress-free packaging, and reduce mechanical stress by precisely controlling temperature and pressure. Low dielectric constant polyimide materials are selected for stress-free packaging because of their excellent thermal stability, mechanical flexibility, and low dielectric constant characteristics. By using low dielectric constant polyimide materials for stress-free packaging, the mechanical stress introduced during the packaging process is significantly reduced, and the single-crystal silicon nanostructure is effectively protected from damage by thermal expansion and mechanical loads. This packaging method not only provides excellent electrical insulation and mechanical protection, but also reduces high-frequency signal loss, and improves the performance and stability of nano devices in complex environments;
[0089] Multi-layer shielding packaging is implemented, and electromagnetic shielding, insulation and mechanical protection are provided for the device through the combination of metal layers, insulating layers and polymer layers. Multi-layer shielding packaging is implemented, and the environmental stability and reliability of the packaged device are effectively improved through the combination of metal, insulating and polymer layers. The metal layer provides electromagnetic shielding, reduces external interference and protects the internal circuit; the insulating layer and polymer layer ensure electrical insulation and mechanical protection to prevent the external environment from damaging the device. The multi-layer shielding packaging design greatly extends the service life of the device and ensures long-term performance stability in harsh environments, providing a solid guarantee for the application of high-performance single-crystal silicon nanochips.
[0090] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.
[0091] Example 1: Single crystal silicon nanochip for high frequency optoelectronic devices
[0092] Preparation of single crystal silicon wafers:
[0093] The Czochralski method is used to grow single crystal silicon rods, and the oxygen content is controlled below 0.5ppm through magnetic field induction technology. Laser cutting technology is used during cutting to cut the silicon rods into silicon wafers with a thickness of 100 to 150 microns, and the cutting accuracy is maintained within ±1 micron.
[0094] Chemical mechanical polishing (CMP) uses a polishing liquid with nano-silicon dioxide particles of 20 to 30 nanometers in diameter, and adds 0.1M hydrofluoric acid as an auxiliary polishing agent. The polishing pressure is set to 0.3 Newtons per square centimeter, and the surface roughness after polishing is controlled to be less than 0.8 nanometers.
[0095] A low temperature annealing treatment is performed with the temperature controlled at 350-400 degrees Celsius for 15 minutes to further reduce the residual stress.
[0096] Multi-stage cleaning and surface preparation:
[0097] A three-step cleaning was performed using a mixed solution of nitric acid (30%), hydrofluoric acid (6%) and ethanol, followed by a 5-minute rinse with ultrapure water. Low-temperature plasma cleaning used alternating treatments of hydrogen and oxygen, with each gas treating for 30 seconds and a total treatment time of 2 minutes.
[0098] Nanostructure Fabrication:
[0099] Multi-level electron beam lithography combined with mask alignment accuracy is controlled at ±4 nanometers, reactive ion etching (RIE) technology is adopted, the etching gas is a mixture of SF6 and C4F8, the RF power is set to 200 watts, and the etching depth accuracy is controlled at ±2 nanometers.
[0100] Surface functionalization:
[0101] A self-assembled monolayer containing trichlorosilane head groups was coated at a temperature of 25 degrees Celsius for 20 minutes, and a protective layer of silicon dioxide was deposited using atomic layer deposition (ALD) technology with a thickness of 2 nanometers.
[0102] Package:
[0103] Polyimide material is used for stress-free packaging, with a packaging temperature of 250 degrees Celsius and a pressure of 0.3 MPa. The multi-layer shielding package includes a 100-nanometer-thick aluminum metal layer, a 700-nanometer-thick silicon nitride insulation layer, and a 10-micron-thick polyimide layer to ensure stability and electromagnetic shielding effect in high-frequency applications.
[0104] Example 2: Single crystal silicon nanowafer for high sensitivity sensor
[0105] Preparation of single crystal silicon wafers:
[0106] The Czochralski method is used to grow low-oxygen single-crystal silicon rods (oxygen content is less than 0.8 ppm), and wire saw cutting is used to set the silicon wafer thickness to 200-250 microns, with the cutting accuracy controlled at ±2 microns.
[0107] Chemical mechanical polishing uses a polishing liquid with nano-silicon dioxide particles of 10 to 15 nanometers in size, combined with diluted nitric acid treatment, and a polishing pressure of 0.2 Newtons per square centimeter, and the final surface roughness reaches less than 0.5 nanometers.
[0108] The annealing temperature is controlled at 300-350 degrees Celsius for 10 minutes to further reduce the residual stress.
[0109] Multi-stage cleaning and surface preparation:
[0110] The cleaning step includes a mixed solution of 30% nitric acid, 5% hydrofluoric acid and anhydrous ethanol, followed by rinsing with ultrapure water for 7 minutes. Low-temperature plasma cleaning uses 100 Pa hydrogen plasma for 1 minute, followed by oxygen plasma for 30 seconds.
[0111] Nanostructure Fabrication:
[0112] Electron beam lithography combines a hard mask (chrome mask) and a soft mask (photoresist), with alignment accuracy maintained within ±3 nanometers. Reactive ion etching uses a mixed gas of SF6 and CHF3, with RF power controlled at 150 watts to ensure sidewall smoothness and verticality.
[0113] Surface functionalization:
[0114] The silicon surface was passivated using a self-assembled monolayer of amino head groups at 35 degrees Celsius for 25 minutes. The protective layer was deposited with aluminum oxide using molecular beam epitaxy (MBE) technology with a thickness of 3 nanometers.
[0115] Package:
[0116] The device is packaged using low dielectric constant polyimide material, with a packaging temperature of 280 degrees Celsius and a pressure of 0.4 MPa. The multi-layer shielding package includes a 150-nanometer copper layer, an 800-nanometer silicon dioxide insulating layer, and a 15-micron polyparaxylene outer layer to ensure the long-term reliability and corrosion resistance of the device in the sensing environment.
[0117] Example 3: High-performance single-crystal silicon nanochip for integrated circuits
[0118] Preparation of single crystal silicon wafers:
[0119] The oxygen content of the single crystal silicon rod grown by the Czochralski method is controlled below 1ppm. The thickness of the silicon wafer is precisely controlled to 50-100 microns by laser cutting, and the cutting accuracy reaches ±0.5 microns.
[0120] The chemical mechanical polishing liquid uses 30 nanometer nano-silicon dioxide particles, the polishing pressure is 0.1 Newton per square centimeter, and 0.05M ammonium fluoride is added to improve the surface flatness. The final surface roughness is less than 0.5 nanometers.
[0121] The low temperature annealing temperature is set at 400-450 degrees Celsius for 12 minutes to optimize the mechanical properties of the wafer and release residual stress.
[0122] Multi-stage cleaning and surface preparation:
[0123] Cleaning uses a mixture of 35% nitric acid, 7% hydrofluoric acid and ethanol, followed by a 10-minute rinse in ultrapure water. Low-temperature plasma cleaning uses oxygen plasma for 3 minutes to ensure complete removal of organic matter and particles.
[0124] Nanostructure Fabrication:
[0125] The combination of electron beam lithography and multi-layer mask alignment keeps the mask alignment accuracy within ±2 nanometers. Reactive ion etching uses a mixed gas of SF6 and 02, with a radio frequency power of 250 watts, and a real-time feedback system to ensure precise control of etching depth and sidewall smoothness.
[0126] Surface functionalization:
[0127] The self-assembled monolayer of trichlorosilane was coated at a reaction temperature of 30 degrees Celsius for 20 minutes. The protective layer was deposited with silicon nitride using atomic layer deposition (ALD) with a thickness of 4 nanometers.
[0128] Package:
[0129] The package is made of polyimide material, with a packaging temperature of 300 degrees Celsius and a pressure of 0.5 MPa. The multi-layer shielding package includes a 200-nanometer aluminum layer, a 900-nanometer aluminum oxide insulation layer, and a 20-micron polyimide outer layer to ensure the electromagnetic compatibility and heat dissipation performance of the integrated circuit.
[0130] Comparative experiment 1: Electrical performance comparison test
[0131] Experimental purpose: To verify the advantages of the present invention in improving the electrical performance of nanochips.
[0132] Experimental setup
[0133] Experimental group (the present invention):
[0134] The process of the invention comprises the steps of multi-level electron beam lithography, multi-layer mask alignment, reactive ion etching, surface functionalization and multi-layer shielding packaging to prepare a single crystal silicon nano wafer.
[0135] Control group 1: Single-crystal silicon nanowafers processed using conventional single-layer electron beam lithography and standard reactive ion etching processes without multi-layer mask alignment and fine surface functionalization.
[0136] Control group 2: Single crystal silicon nanowafers using wet etching technology and simple thermal oxidation surface passivation process, without using high-precision photolithography and complex surface treatment.
[0137] Control group 3: single crystal silicon nanowafers processed using standard electron beam lithography and reactive ion etching but without protective layer deposition.
[0138] Experimental procedures
[0139] Sample preparation:
[0140] The experimental group and each control group prepared single-crystal silicon nanochips according to their respective process routes to ensure that the sample size, thickness and basic design of the nanostructure were consistent for fair comparison.
[0141] Electrical performance test:
[0142] The carrier mobility was measured using a Hall effect tester.
[0143] The resistivity of the wafer was tested using a four-probe method.
[0144] The leakage current characteristics of the wafer were measured using an IV curve test system.
[0145] Data Records:
[0146] Under the same environmental conditions (room temperature, relative humidity 40%), each group of samples was tested repeatedly, and the measurement data were recorded three times and the average value was calculated.
[0147] The comparative experimental data are shown in Table 1:
[0148] Table 1 Electrical performance comparison test data table
[0149]
[0150] From the data in Table 1, we can get:
[0151] The average migration rate of the experimental group was 1503 cm 2 / V·s, which is much higher than that of all control groups, indicating that the process of the present invention can effectively reduce nanostructure and surface defects, thereby improving the mobility efficiency of carriers;
[0152] The average resistivity of the experimental group was 0.005Ω·cm, which was significantly lower than that of all control groups, showing the superiority of the process of the present invention in nanostructure manufacturing accuracy and surface passivation.
[0153] The experimental group had the lowest leakage current, averaging 0.8 nA, which indicates that the multi-layer shielding package and surface functionalization of the present invention can significantly reduce the leakage path and improve the electrical isolation performance of the chip;
[0154] This verifies the significant advantages of the present invention in optimizing electrical performance.
[0155] Comparative experiment 2: Surface functionalization and environmental stability comparison test
[0156] Experimental purpose: To verify the advantages of the present invention in improving the chemical stability and environmental tolerance of the nanostructure surface.
[0157] Experimental setup
[0158] Experimental group (the present invention):
[0159] The process of the present invention was used, including coating a self-assembled monolayer (SAM) and depositing a protective layer with a thickness of 2 nanometers by atomic layer deposition (ALD).
[0160] Control group 1: Surface passivation was performed using conventional thermal oxidation without self-assembled monolayer or protective layer deposition.
[0161] Control group 2: After wet chemical passivation (hydrofluoric acid treatment), a single layer of silane coupling agent was applied as surface functionalization treatment.
[0162] Control group 3: No surface functionalization treatment was performed, only basic cleaning was performed.
[0163] Experimental procedures
[0164] Sample preparation:
[0165] Each group of samples was surface functionalized according to its own process route, ensuring that the samples were surface treated on the same nanostructure basis to ensure fairness in the comparison.
[0166] Environmental stability test:
[0167] Each group of samples was placed in high humidity (85% RH), acidic environment (pH 4) and high temperature (85° C.) conditions and subjected to 100 hours of exposure test.
[0168] Samples were taken out every 20 hours, and X-ray photoelectron spectroscopy (XPS) was used to detect changes in the chemical composition of the surface and evaluate the stability of the surface passivation.
[0169] Electrochemical impedance spectroscopy (EIS) was used to measure the changes in the electrical properties of the samples, especially the changes in interfacial resistance and capacitance.
[0170] Data Records:
[0171] The tests were carried out under the same conditions, and the changes in chemical composition (such as the presence of oxides and carbides) and electrical properties were recorded.
[0172] The comparative experimental data are shown in Table 2:
[0173] Table 2 Comparative test data of surface functionalization and environmental stability
[0174]
[0175] From Table 2, we can get:
[0176] The experimental group showed excellent surface stability and electrical property retention ability under high humidity, acidic and high temperature environments. Compared with the control group, the self-assembled monolayer and atomic layer deposition protective layer of the present invention effectively inhibited surface oxidation and carbonization reactions, maintained low interface resistance and capacitance, and ensured the long-term stability of the nanochip in harsh environments. The experiment verified the innovation and practical value of the present invention in improving the environmental tolerance and electrical stability of single crystal silicon nanostructures.
[0177] Comparative experiment 3: packaging performance comparison test
[0178] Experimental purpose: To verify the advantages of the present invention in improving the environmental tolerance, mechanical stability and electromagnetic shielding performance of nanochips.
[0179] Experimental setup
[0180] Experimental group (the present invention):
[0181] Use low dielectric constant polyimide material for stress-free packaging, combined with multi-layer shielding packaging (including metal layers, insulation layers and polymer layers).
[0182] Control group 1: Used conventional epoxy encapsulation without any special stress control or multi-layer shielding design.
[0183] Control group 2: Standard polyimide encapsulation was used, but no multi-layer shielding was implemented, providing only basic mechanical protection.
[0184] Control group 3: Silicon rubber material was used for flexible packaging, mainly for mechanical protection, without electromagnetic shielding design.
[0185] Experimental procedures
[0186] Sample preparation:
[0187] The experimental group and each control group encapsulated the single crystal silicon nanochip according to their respective encapsulation process routes to ensure that the nanostructure and surface treatment were consistent to eliminate the influence of structural differences on the experimental results.
[0188] Packaging performance test:
[0189] Temperature cycle test: The packaged samples are subjected to temperature cycles in an environment of -40 to 125 degrees Celsius, with each cycle lasting 30 minutes and a total of 100 cycles to test the thermal stability and mechanical strain response of the package.
[0190] Electromagnetic Interference (EMI) Shielding Test: Use standard EMI test equipment to measure the electromagnetic shielding effectiveness of each packaged sample in the frequency range of 1 to 10 GHz to evaluate its effect in suppressing external electromagnetic interference.
[0191] Mechanical vibration test: The sample is placed on a vibration test bench with a frequency range of 20 to 2000 Hz, an amplitude of 0.5 G, and a test time of 1 hour to evaluate the mechanical stability of the package.
[0192] Data Records:
[0193] Each group of samples was tested under the same conditions, and the data of mechanical strain, electromagnetic shielding effectiveness and vibration stability were recorded.
[0194] The comparative experimental data are shown in Table 3:
[0195] Table 3 Packaging performance comparison test data table
[0196]
[0197] From the data in Table 3, we can get:
[0198] The strain of the experimental group is very small (0.2% on average), much lower than that of all control groups, which shows that the stress-free package of the present invention can effectively alleviate the thermal stress caused by temperature changes and ensure the structural stability of the chip;
[0199] The strain of the experimental group is very small (average 0.2%), much lower than that of all control groups. This shows that the stress-free packaging of the present invention can effectively alleviate the thermal stress caused by temperature changes and ensure the structural stability of the chip;
[0200] The experimental group had the highest vibration stability score (9 on average), indicating that under mechanical vibration conditions, the package of the present invention can provide excellent mechanical protection and maintain the integrity of the nanostructure.
[0201] This verifies the innovative advantages of the "high-performance single-crystal silicon nanochip manufacturing process" of the present invention in packaging design.
[0202] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-performance single-crystal silicon nanochip manufacturing process, characterized in that: The following steps are involved: Prepare single crystal silicon wafers, and obtain high-quality single crystal silicon wafers through fine cutting, chemical mechanical polishing and surface residual stress elimination treatment; Multi-stage cleaning and surface treatment to remove surface contaminants through a combination of molecular chromatography, electric field-assisted ultrasonic cleaning, and low-temperature plasma cleaning; Nanostructure manufacturing, using multi-stage electron beam lithography, segmented reactive ion etching and adaptive deep etching control to form complex nanostructures; Doping and heat treatment, using dynamic time segmented annealing and multi-scale environmental control for doping activation and defect repair; Surface functionalization and packaging improve the environmental stability and long-term reliability of chips through self-assembled monolayer deposition, molecular beam epitaxy and multi-level high-precision packaging.
2. The high performance single crystal silicon nano wafer manufacturing process according to claim 1, characterized in that: The dynamic time segmented annealing and multi-scale environmental regulation include: The annealing temperature and time are adjusted in stages. The temperature is controlled at 300-500 degrees Celsius in the initial stage, and stress is released by low-frequency short pulses with each pulse lasting 5-10 seconds. The temperature in the middle stage is set at 600-800 degrees Celsius, and the activation and diffusion of dopants are achieved by increasing the pulse frequency to once every 10-20 seconds and controlling the pulse temperature fluctuation at 50-100 degrees Celsius; In the final stage, the temperature is controlled at 800-1000 degrees Celsius, the pulse frequency is gradually reduced and the temperature step method is used to adjust 10-20 degrees Celsius every 5 minutes to optimize the repair of lattice defects; Combining real-time stress sensing and defect analysis data, the annealing parameters are adjusted through a reinforcement learning algorithm to achieve an adaptive annealing process.
3. The high performance single crystal silicon nano wafer manufacturing process according to claim 2, characterized in that: The multi-scale environmental regulation includes: In the initial stage, high-purity argon gas is used for overall atmosphere control, with a flow rate of 1 to 2 liters per minute; In the mid-term, the molecular sieve adjustment system is used to fine-tune the atmosphere through molecular diversion technology, removing the oxygen concentration to less than 5ppm and accurately controlling the hydrogen concentration at 0.1-0.3%; In the final stage, the amount of hydrogen introduced is fine-tuned to 10-100 ml / min through a local regulating valve to promote surface passivation and defect repair.
4. The high performance single crystal silicon nano wafer manufacturing process according to claim 1, characterized in that: The preparation of a single crystal silicon wafer comprises: The Czochralski method is used to grow single crystal silicon rods, and the oxygen content is controlled to be less than 1ppm through magnetic field induction technology; Cut the single crystal silicon rod into silicon wafers with a thickness of 50 to 300 microns by vibration-controlled wire saw or laser cutting, with a cutting accuracy of ±2 microns; Chemical mechanical polishing combined with weak acid treatment is used to eliminate surface microcracks. 10 to 50 nanometers of nano-silicon dioxide is added to the polishing liquid, and the polishing pressure is controlled at 0.1 to 0.5 Newtons per square centimeter. A low-temperature short-time annealing is performed with the temperature controlled at 300 to 500 degrees Celsius for 10 to 20 minutes to reduce residual stress, and the final surface roughness is less than 1 nanometer.
5. The high performance single crystal silicon nano wafer manufacturing process according to claim 1, characterized in that: The multi-stage cleaning and surface treatment includes: A three-step cleaning process using a mixed solution of nitric acid, hydrofluoric acid, and ethanol gradually removes heavy metal ions, oxides, and organic matter; Ultrapure water is used for rinsing, and ultrapure water is dynamically regenerated by electrolysis. The rinsing time is 5 to 10 minutes; Low-temperature plasma cleaning uses alternating hydrogen and oxygen plasma treatments to ensure complete removal of residual contaminants.
6. The high performance single crystal silicon nano wafer manufacturing process according to claim 5, characterized in that: The cleaning further comprises: Ammonium hydroxide and hydrogen peroxide are added to the cleaning solution, and cleaning is performed with the assistance of dual-frequency ultrasound at 20 to 80 kHz and an electric field at 10 to 20 volts per centimeter to improve the desorption efficiency of particles and organic matter; By real-time monitoring of the conductivity of the cleaning fluid, the cleaning effect is ensured to be continuous and stable, and the cleaning fluid is automatically replaced.
7. The high performance single crystal silicon nano wafer manufacturing process according to claim 1, characterized in that: The nanostructure manufacturing comprises: Using multi-level electron beam lithography and multi-layer mask alignment technology, the mask alignment accuracy is controlled within ±5 nanometers to achieve the superposition of complex nano patterns; Using reactive ion etching, the etching parameters are monitored by a real-time feedback system to ensure consistent etch depth and sidewall smoothness.
8. The high performance single crystal silicon nano wafer manufacturing process according to claim 7, characterized in that: The nanostructure manufacturing further comprises: Implement ultra-fast pulse etching, with each pulse lasting 1 to 5 milliseconds, and control the etching effect by adjusting the pulse interval and frequency; Combined with a multi-layer mask protection strategy, the lateral corrosion of the mask and the sidewall erosion of the pattern are reduced to ensure the verticality and precision of the nanostructure.
9. The high performance single crystal silicon nano wafer manufacturing process according to claim 1, characterized in that: The surface functionalization includes: Coating a self-assembled monolayer on the surface of the nanostructure, using atomic layer deposition or molecular beam epitaxy to deposit a protective layer with a thickness of 1 to 5 nanometers; Real-time thickness monitoring ensures uniformity and surface smoothness of the protective layer, improving the environmental tolerance of the nanostructure.
10. The high performance single crystal silicon nano wafer manufacturing process according to claim 1, characterized in that: The package includes: Use low dielectric constant polyimide materials for stress-free packaging, and reduce mechanical stress by precisely controlling temperature and pressure; Multi-layer shielding packaging is implemented to provide electromagnetic shielding, insulation and mechanical protection for the device through a combination of metal layers, insulating layers and polymer layers.
Citation Information
Cited By
Preparation method of single-walled carbon nanotube
CN120097327A
Surface processing technology for diode
CN120116031A
Chained single-side chemical cleaning system for multilayer silicon wafers
CN120674350A
Intelligent sensor semiconductor wafer preparation method based on vapor deposition
CN120864805A
Method for the preparation of smart sensor semiconductor wafers based on vapor deposition
CN120864805B